2017
DOI: 10.1101/121228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosynthesis of Isonitrile Lipopeptides by Conserved Non-ribosomal Peptide Synthetase Gene Clusters inActinobacteria

Abstract: A putative lipopeptide biosynthetic gene cluster is conserved in many species of Actinobacteria, including Mycobacterium tuberculosis and M. marinum, but the specific function of the encoding proteins has been elusive. Using both in vivo heterologous reconstitution and in intro biochemical analyses, we have revealed that the five encoding biosynthetic enzymes are capable of synthesizing a new family of isonitrile lipopeptides (INLPs) through a thio-template mechanism. The biosynthesis features the generation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it was shown to negatively regulate the oxidoreductase Rv0068 in order to alter the sensitivity of M.tb to INH (Yang et al, 2019). The gene rv0096 encodes a putative member of the PPE (proline-glutamate and proline-proline-glutamate) family and is part of the operon rv0096-rv0101 that was shown to produce a virulence-related lipopeptide (Hotter et al, 2005;Wang et al, 2007;Liu et al, 2013;Harris et al, 2017). In addition, it was shown that a loss of function mutation of rv0096 in multi-drug resistant M.tb strains conferred resistance to D-cycloserine (Desjardins et al, 2016).…”
Section: Mycobacterium Tuberculosis Mutantsmentioning
confidence: 99%
“…Moreover, it was shown to negatively regulate the oxidoreductase Rv0068 in order to alter the sensitivity of M.tb to INH (Yang et al, 2019). The gene rv0096 encodes a putative member of the PPE (proline-glutamate and proline-proline-glutamate) family and is part of the operon rv0096-rv0101 that was shown to produce a virulence-related lipopeptide (Hotter et al, 2005;Wang et al, 2007;Liu et al, 2013;Harris et al, 2017). In addition, it was shown that a loss of function mutation of rv0096 in multi-drug resistant M.tb strains conferred resistance to D-cycloserine (Desjardins et al, 2016).…”
Section: Mycobacterium Tuberculosis Mutantsmentioning
confidence: 99%